2017
DOI: 10.1111/ajt.14234
|View full text |Cite|
|
Sign up to set email alerts
|

Thrombalexin: Use of a Cytotopic Anticoagulant to Reduce Thrombotic Microangiopathy in a Highly Sensitized Model of Kidney Transplantation

Abstract: Early activation of coagulation is an important factor in the initiation of innate immunity, as characterized by thrombotic microangiopathy (TMA). In transplantation, systemic anti-coagulation is difficult due to bleeding. A novel ‘cytotopic’ agent, ‘Thrombalexin’, (TLN) combines a cell-membrane bound (mirystoyl tail) anti-thrombin (HLL peptide) which can be perfused directly to the donor organ or cells. Thromboelastography (TEG) was used to measure time to clot formation (r-time) in both rhesus and human bloo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 28 publications
1
17
0
Order By: Relevance
“…Aortas from these mice, when transplanted into apolipoprotein E (ApoE)À/ À mice fed a high-fat diet, fail to express CCL2 and MIF and do not develop atherosclerosis, in contrast to the florid lesions seen in control WT aortas (Chen et al, 2020). Recently, we have reported pretransplant perfusion into rat or primate organs with PTL060 (or related compounds) prevents the intravascular thrombosis associated with AMR (Manook et al, 2017;Karegli et al, 2017). Most recently, we have showed that intravenous delivery of PTL060 into ApoEÀ/À mice fed a high-fat diet leads to widespread coating of the endothelium, inhibits expression of both CCL2 and MIF, and prevents atheroma formation (Chen et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Aortas from these mice, when transplanted into apolipoprotein E (ApoE)À/ À mice fed a high-fat diet, fail to express CCL2 and MIF and do not develop atherosclerosis, in contrast to the florid lesions seen in control WT aortas (Chen et al, 2020). Recently, we have reported pretransplant perfusion into rat or primate organs with PTL060 (or related compounds) prevents the intravascular thrombosis associated with AMR (Manook et al, 2017;Karegli et al, 2017). Most recently, we have showed that intravenous delivery of PTL060 into ApoEÀ/À mice fed a high-fat diet leads to widespread coating of the endothelium, inhibits expression of both CCL2 and MIF, and prevents atheroma formation (Chen et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…However, the literature suggests that VETs can be used as an adjunct to CCTs when guiding therapy in these conditions. 168,176 Owing to the scarce literature, the utilization of VETs in the diagnosis and treatment of these conditions warrants further investigation.…”
Section: Microangiopathic Hemolytic Anemiasmentioning
confidence: 99%
“…Literature regarding the use of VETs in thrombotic thrombocytopenic purpura also highlights the limitations of VETs in its diagnosis. However, the literature suggests that VETs can be used as an adjunct to CCTs when guiding therapy in these conditions 168,176 . Owing to the scarce literature, the utilization of VETs in the diagnosis and treatment of these conditions warrants further investigation.…”
Section: Benign Hematologic Disordersmentioning
confidence: 99%
“…156 The activation of the coagulation cascade by antibody and complement has prompted investigation of anti-complement strategies to prevent AMR in NHP models, as agents developed for human use often cannot be interrogated directly in rodent models and preclinical trials are mandated by ethical considerations. 4,157 Protective immunity in immunosuppressed solid organ transplant recipients…”
Section: Nhp Models Of Antibody-mediated Rejectionmentioning
confidence: 99%